Effect of non-linear absorption on characteristics of laser-induced luminescence - Zelensky, S.E.; Okhrimenko, B.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
This paper deals with the methodology of laser-induced luminescence at high excitation levels. For a case when a photodetector collects integral (over the volume) luminescence power, a method is proposed for processing the experimentally-measured luminescence power and optical transmittance as some functions of the incident laser power. The method is based on the analysis of relative increments of luminescence and transmitted laser power. Considered are two examples of mechanisms of non-linear laser-induced luminescence, namely: saturated molecular luminescence and luminescence excited via two-photon absorption.